Penggunaan Media Pembelajaran Berupa Group Whatsapp terhadap Hasil Belajar PPKn Siswa Kelas II SDN Pekojan 02 Petang Kota Jakarta - Kistiningrum, Annisa; Sa'odah, Sa'odah; Hasan, Najib (MASALIQ, 2022)
This study aims to obtain information on the effectiveness of using WhatsApp media on student learning outcomes. This research uses qualitative research method with descriptive analysis method. In this study, there were 2 related respondents from SDN Pekojan 02 Petang Jakarta, consisting of one teacher and one student. Interviews were conducted in a structured manner with questions compiled and linked and developed with related literature. The results of this study are the ineffective use of Whatsapp media due to the lack of facilities and infrastructure and the unpreparedness of technology education.